2007
DOI: 10.1128/aac.00538-07
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibilities and Clinical Sources ofDialisterSpecies

Abstract: Seventy-four strains representing the four species of the genus Dialister were isolated from various clinical samples. Dialister pneumosintes and Dialister micraerophilus were the two mainly encountered species. Fifty-five isolates were tested against 14 antimicrobial agents. Decreased susceptibilities to piperacillin, metronidazole, macrolides, fluoroquinolones, and rifampin were demonstrated. The clinical impact of these decreased susceptibilities remains to be investigated but should prompt microbiologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 18 publications
5
35
1
Order By: Relevance
“…Morio et al investigated 33 isolates of D. pneumosintes obtained at their hospital in France (21) and reported that there were no cases of resistance to any betalactam agents, fluoroquinolones or metronidazole, similar to the findings of previous cases (19) and the current case, with the exception of susceptibility to penicillin. In the present case, we initially administered cefepime and subsequently added levofloxacin.…”
Section: Pneumosintes Formerly Bacteroides Pneumosintes Is An Obsupporting
confidence: 71%
“…Morio et al investigated 33 isolates of D. pneumosintes obtained at their hospital in France (21) and reported that there were no cases of resistance to any betalactam agents, fluoroquinolones or metronidazole, similar to the findings of previous cases (19) and the current case, with the exception of susceptibility to penicillin. In the present case, we initially administered cefepime and subsequently added levofloxacin.…”
Section: Pneumosintes Formerly Bacteroides Pneumosintes Is An Obsupporting
confidence: 71%
“…In HLA-B27 negative-ERA patients, we found Haemophilus and Eggerthella , recently associated with rheumatoid arthritis (Zhang et al, 2015; Chen et al, 2016). Moreover, when considering only the ERA group, in HLA-B27 positive patients we also showed enrichment of Lactobacillus , observed as potential arthritogenic agent via its cell wall pepetidoglycan (Severijnen et al, 1989), Clostridium cluster XI , that includes C. difficile , a well-known proinflammatory and colitis inducing-bacterium, and Dialister , frequently found in periodontitis and other infections (Morio et al, 2007). …”
Section: Discussionmentioning
confidence: 84%
“…Whether relapses may be due to re-infections accompanying intercourse remains controversial [29], [30]. Systematically administered metronidazole has little or no activity against M. hominis , Bifidobacterium , and G. vaginalis and only moderate activity against Dialister [31], [32]. Metronidazole has predictable activity against Prevotella , Leptotrichia , and Eggerthella [33], [34].…”
Section: Discussionmentioning
confidence: 99%